Method for estimating cycle performance of electrode material of rechargeable battery
Through the positron annihilation life spectrum technology, the cycle performance of electrode materials is quickly collected and analyzed, and the cycle performance of electrode materials in the existing technology is solved, and the cycle life test of electrode materials is quickly and accurately evaluated, which improves the battery R&D efficiency.
Patent Information
- Application Number
- CN202411291620.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
The cycle life test method of battery electrode materials in the prior art takes a long time, and it is impossible to accurately judge the life of the electrode material. The test process is complex and costly, making it difficult to quickly evaluate the cycle performance of the electrode material.
The positron annihilation life spectrum technology is used to quickly estimate the cycling performance of the electrode material by collecting the positron annihilation life and intensity of the battery sample in the initial and post-cycle states, and combining with the PALSfit3 software despectral fitting.
It realizes a rapid estimate of the cycle life of the electrode material, reduces the cost of battery R&D, improves R&D efficiency, overcomes the shortcomings of traditional testing methods, and can accurately estimate the cycle performance of the electrode material.
Smart Images

Figure CN119147999A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for estimating the cycle performance of an electrode material of a rechargeable battery, and in particular to a method for quickly estimating the cycle performance of an electrode material of a rechargeable battery, and belongs to the field of battery testing. Background Art
[0002] Rechargeable batteries have become a widely used electrochemical energy storage technology due to their advantages such as high energy density and long cycle life (especially lithium batteries), and are also the focus of current energy storage technology research. With the development of science and technology, rechargeable batteries have rapidly become the main energy source for smartphones, laptops, electric scooters and electric vehicles. In recent years, the demand for rechargeable batteries with high stability, high rate, high capacity and fast charging has gradually increased. However, as the number of charge and discharge cycles increases, the electrode materials and electrolytes inside the battery will inevitably age. Even if there are no design defects and production quality problems, the battery will have problems such as structural instability, decreased capacity, and slower charge and discharge rates. Among them, the cycle life performance of the electrode material is extremely important, which directly determines the working life and long-term stability of the battery. Therefore, in the process of research and development of electrode materials, it is often necessary to test the cycle performance of the electrode material and then evaluate its industrial application prospects.
[0003] At present, the cycle life test methods of battery electrode materials are usually divided into two types: long-term electrochemical performance test and physical and chemical property test during the cycle, as follows:
[0004] (A) Long-term electrochemical performance testing.
[0005] Through the external test data line, the battery is placed in the battery measurement system to measure the electrochemical properties of the battery for a long time, such as charge and discharge cycle test, battery capacity retention test, battery internal resistance test, cycle efficiency test, battery self-discharge test, electrochemical impedance, overcharge and over-discharge test, etc., and the life of the electrode material and the charge and discharge performance are judged based on the attenuation of the output data.
[0006] The electrochemical performance test method has the following defects: (1) The measurement time is extremely long. The test of long-life electrode materials often takes several months or even longer. (2) The cause of performance degradation cannot be attributed to the electrode material alone. Only the overall performance degradation of the battery and the overall life of the battery can be measured, so the cycle performance of the electrode material cannot be accurately determined. (3) Only performance degradation can be tested, and it is difficult to determine the internal reasons for the long life of the electrode material.
[0007] (ii) Testing of physical and chemical properties during circulation.
[0008] By conducting conventional physical and chemical property tests on electrode materials during the cycle process, and judging their cycle stability and cycle life based on experience, for example, using X-ray diffraction to study the changes in the crystal structure of electrode materials during the cycle process, using scanning electron microscopy to observe changes in the electrode surface and microstructure, using transmission electron microscopy to analyze the microstructure and defects of electrode materials, using X-ray photoelectron spectroscopy to analyze the surface chemical composition and its changes of electrode materials, using Raman spectroscopy to detect the structure and phase changes in electrode materials, and using thermal stability tests to measure the stability and cycle performance of electrode materials at high or low temperatures.
[0009] The physical and chemical property testing method has the following defects: (1) The electrode material does not show significant changes in crystal form or morphology in the early stage of the cycle, so the measurement takes a long time. The test of long-life electrode materials often takes 1 month or even longer. (2) The measurement requires disassembling the battery and measuring the electrode material. The battery cannot be restored after disassembly. (3) Lithium battery disassembly is dangerous and requires special venues and equipment. The difficulty and cost of disassembly are both high, which also makes the testing process more complicated and the cycle longer. Summary of the invention
[0010] In view of the shortcomings of the prior art, the present invention aims to provide a new method for estimating the cycle performance of an electrode material of a rechargeable battery.
[0011] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0012] A method for estimating the cycle performance of an electrode material of a rechargeable battery comprises the following steps:
[0013] S1. Assembling the electrode materials to be tested to form a battery sample;
[0014] Wherein, the battery sample is a half-battery or a full-battery;
[0015] S2, charging and discharging the battery sample obtained in S1 for the first time, so that the battery sample reaches an initial operating state;
[0016] S3, placing a positron radiation source close to the outer surface of the battery sample, collecting the positron annihilation lifetime spectrum of the battery sample at this time, decomposing and fitting the spectrum, and obtaining the positron annihilation lifetime and intensity in the initial state;
[0017] Wherein, the outer surface is the area of the outer shell of the battery sample close to the location of the electrode material;
[0018] S4, performing a charge and discharge cycle on the battery sample for at least one cycle;
[0019] S5, placing a positron radiation source close to the outer surface of the battery sample, collecting the positron annihilation lifetime spectrum of the battery sample at this time, decomposing and fitting the spectrum, and obtaining the positron annihilation lifetime and intensity in the cycled state;
[0020] Wherein, the outer surface is the area of the outer shell of the battery sample close to the location of the electrode material;
[0021] S6. Estimate the cycle performance of the electrode material according to the changes in the positron annihilation lifetime and intensity in the initial state and the positron annihilation lifetime and intensity in the cycled state.
[0022] Furthermore, in S1, the electrode material, the conductive agent and the binder are mixed in a mass ratio of 7-9:0.5-1.5:1, and an appropriate amount of solvent is added to the obtained mixture (based on the slurry being honey-like, generally 10-20 drops of solvent are added to every 100 mg of the mixture), and the mixture is ground evenly to obtain a slurry; the slurry is then coated on the current collector, dried, and cut to obtain pole pieces; and the pole pieces are then assembled to form a battery sample.
[0023] Furthermore, the conductive agent includes Super P (small particle conductive carbon black).
[0024] Furthermore, the binder includes PVDF.
[0025] Furthermore, the solvent includes NMP (N-methylpyrrolidone).
[0026] Further, in S3 and / or S5, a baffle is placed on the surface of the positron radiation source away from the outer surface to form a "sandwich" structure, and then the "sandwich" structure is placed in a collection probe of a positron annihilation lifetime spectrometer to collect a positron annihilation lifetime spectrum;
[0027] Wherein, the baffle is made of a material with a known positron annihilation lifetime;
[0028] Preferably, the baffle is a metal sheet, more preferably a nickel sheet; more preferably, the nickel sheet is obtained by annealing a pure nickel sheet at 660-700° C. in argon for 8-12 hours.
[0029] Preferably, the thickness of the baffle is ≥1 mm, more preferably 2-10 mm.
[0030] Preferably, the thickness of the outer shell is ≤1 mm, thereby better meeting the detection requirements of the positron annihilation lifetime spectrum collection process.
[0031] More preferably, the thickness of the outer shell is 0.1-0.3 mm, and even more preferably 0.2-0.3 mm.
[0032] Furthermore, PALSfit3 software was used for spectrum fitting.
[0033] Furthermore, in S4, the cycle is 2-100 times, further 3-90 times, and preferably 10-80 times.
[0034] Furthermore, in S4, the charge-discharge cycle rate is 0.1-10C, preferably 0.5-5C, and more preferably 1-3C.
[0035] Furthermore, in S4, the battery sample is charged and discharged for 10 cycles at a rate of 1C.
[0036] Further, in S6, when △T1<2%, △I1<2%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is ≥400 cycles;
[0037] When 2%≤△T1<10%, 2%≤△I1, △T2<2%, the charge and discharge cycle life of the battery sample is 100-399 cycles;
[0038] When 10%≤△T1,△T2≥2%, the charge-discharge cycle life of the battery sample is ≤99 cycles;
[0039] The charge and discharge cycle life of the battery sample refers to the number of charge and discharge cycles required for the capacity retention rate of the battery sample to drop below 80% of the initial capacity when the battery sample is charged and discharged at the same rate in the charge and discharge cycle process in S4;
[0040]
[0041]
[0042]
[0043]
[0044] T1 is the short life in the initial state, and T1' is the short life in the post-cycle state;
[0045] T2 is the long life in the initial state, and T1′ is the long life in the post-cycle state;
[0046] I1 is the positron intensity 1 in the initial state, and I1' is the positron intensity 1 in the state after the cycle;
[0047] I2 is the positron intensity 2 in the initial state, and I2' is the positron intensity 2 in the state after the cycle.
[0048] Generally, the positron annihilation lifetime and intensity can be divided into two lifetime and intensity pairs. Lifetime 1 is a short lifetime (generally in the range of 100-600Ps, T1, T1'), which is generally the bulk annihilation lifetime of the active material. The increase in value reflects the increase in the size or cracking of the bulk defects of the active material. The corresponding intensity 1 (I1, I1') reflects the proportion of the bulk in the material and the change in the density of defects. Lifetime 2 is a long lifetime (generally greater than 1000Ps, T2, T2'), which generally comes from the binder in the electrode material and the multiple interface positions of the material. The increase in value reflects the increase in the free volume of the electrode material, the increase in looseness or the generation of large pores at the interface, which all mean the aging of the electrode material. The corresponding intensity 2 (I2, I2') value increases reflect the increase in the amount of free volume inside the binder and the multiple interface positions of the material, or the cracking of the electrode causing partial electrolyte infiltration.
[0049] Further, when 2%≤△T1<5%, 2%≤△I1<5%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is 200-399 cycles;
[0050] When 5%≤△T1<10%, 5%≤△I1, △T2<2%, △I2≥1%, the charge and discharge cycle life of the battery sample is 100-199 cycles.
[0051] Furthermore, the rechargeable battery includes one or more of a lithium battery, a sodium battery, a lead-acid battery, a nickel-cadmium battery, and a nickel-metal hydride battery.
[0052] Furthermore, the electrode material is a positive electrode material or a negative electrode material; the negative electrode material includes a silicon-based negative electrode material.
[0053] Furthermore, the silicon-based negative electrode material includes one or more of nano silicon powder, porous nano silicon powder, and carbon nanotube-coated porous nano silicon powder.
[0054] Optionally, the preparation method of carbon nanotube-coated porous nano-silicon powder includes the following steps: mixing carbon nanotubes and nano-silicon powder in a mass ratio of 0.8-1.2, placing the resulting mixture in a ball mill, and adding stainless steel beads; wherein the mass ratio of stainless steel beads to the mixture is 110-120:1; fixing the ball mill on a planetary ball mill, and ball milling at 600rpm for 2h to obtain carbon nanotube-coated porous nano-silicon powder.
[0055] Furthermore, the positron radiation source is a point-shaped positron radiation source.
[0056] Furthermore, in S2, the first charge and discharge rate of the battery sample obtained in S1 is 0.1-3C, preferably 0.3-1.5C, and more preferably 0.5-1C.
[0057] Positron annihilation technology is a means of detecting the internal structure of materials and is an application of low-energy nuclear physics. Among them, positrons are the antimatter of electrons. In condensed matter, they can easily diffuse to vacancy defects, nanopores, free volumes, special nanoclusters, interface defects of grain boundaries and other locations for annihilation. The annihilation characteristics are closely related to the defect size, density, electron cloud, chemical environment, etc. at the capture location. Among them, the spectrum analysis results will include a certain number of positron annihilation lifetimes and corresponding positron annihilation intensities. Generally speaking, each pair of positron annihilation lifetimes and positron annihilation intensities can reflect the size and relative density of a certain vacancy in the sample being tested. Different pairs of positron annihilation lifetimes and positron annihilation intensities reflect the size and relative density of different types of vacancies.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) The method of the present invention measures the positron annihilation lifetime and intensity of the battery sample to be tested after the first charge and after a small number of cycles. According to the changes in the positron annihilation lifetime and intensity, the cycle life performance of the electrode material of the corresponding rechargeable battery can be quickly estimated, thereby providing a new method for estimating the cycle performance of the electrode material.
[0060] (2) The method of the present invention can quickly estimate the range of cycle life of electrode materials, which can facilitate the research and development of corresponding rechargeable batteries or electrode materials, overcome the many defects of traditional electrochemical performance testing through battery measurement systems, and can also overcome the related defects of directly testing the physical and chemical properties of electrode materials, which helps to reduce the research and development costs of rechargeable batteries or electrode materials and improve research and development efficiency. In particular, the method of the present invention can accurately estimate the cycle performance of electrode materials and electrode materials after physical modification and / or chemical modification. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 It is a schematic diagram of the button-type half-cell, positron radiation source, and baffle assembly of Example 1 of the present invention.
[0062] In the figure, 1-button half-cell, 2-positron radiation source, 3-shield. DETAILED DESCRIPTION
[0063] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0064] Example 1
[0065] Rapidly predict the cycle life of pure nano-silicon powder (average particle size 100nm) negative electrode material. The test electrode is applied to the half-cell of button lithium battery, including the following steps:
[0066] (1) Nano silicon powder with an average particle size of 100 nm is used as the active material. Nano silicon powder, Super P (small particle conductive carbon black), and PVDF are mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP (N-methylpyrrolidone, 15 drops of solvent are added to every 100 mg of the mixture) is added to the resulting mixture, and the mixture is put into a mortar and ground into a slurry. The slurry is coated on a copper foil, and the thickness of the negative electrode layer is 600 microns after drying. The nano silicon negative electrode sheet is cut to obtain a button-type half-cell based on the prepared nano silicon negative electrode sheet. The assembly needs to be completed in a vacuum glove box with an argon atmosphere.
[0067] (2) After the battery assembly is completed, the button-type half-cell is clamped into a battery testing system (Xinwei CT-4008Tn), and the button-type half-cell is charged and discharged for the first time (the charge and discharge rate is 0.5C) to make the battery reach the initial operating state.
[0068] (3) See Figure 1 , a point positron radiation source is placed on the outer surface of the anode of the button half-cell (i.e., close to the position of the silicon negative electrode material), a baffle is placed on the surface of the positron radiation source away from the outer surface to form a "sandwich" structure, and then the "sandwich" structure is placed in the acquisition probe of the positron annihilation lifetime spectrometer (Japan TechAP positron annihilation spectrometer), the positron annihilation lifetime spectrum is collected, and the spectrum is analyzed by PALSfit3 spectrum analysis software. The spectrum analysis process (general positron annihilation lifetime spectrum analysis method, detailed description of the spectrum analysis software download page: https: / / palsfit.dk / ) deducts the annihilation lifetime of positrons in the radiation source itself, the battery casing, the copper foil, etc., to obtain the positron annihilation lifetime and intensity in the silicon-based negative electrode material in the initial state, which is recorded as state A1.
[0069] (3) The button-type half-cell is clamped into the battery testing system described in step (2) and charged and discharged for 10 cycles at a rate of 1C.
[0070] At this time, the energy retention rate of the button half-cell is high, and the capacity decay is not obvious (the capacity retention rate is higher than 97%), and it is impossible to rely on conventional methods to judge the life of the electrode material.
[0071] (4) The battery is removed, and a point-shaped positron radiation source is placed on the outer surface of the anode of the button-type half-cell (i.e., close to the position of the silicon negative electrode material), and a baffle (annealed nickel sheet, 0.1 mm thick, obtained by annealing a pure nickel sheet at 680°C in argon for 10 hours) is placed on the surface of the positron radiation source away from the outer surface to form a "sandwich" structure. The "sandwich" structure is then placed in the acquisition probe of the positron annihilation lifetime spectrometer to collect the positron annihilation lifetime spectrum, and the spectrum is analyzed using the PALSfit3 spectrum analysis software. The spectrum analysis process deducts the annihilation lifetime of the positrons between the radiation source itself, the battery casing, the copper foil, etc., to obtain the positron annihilation lifetime and intensity in the middle of the silicon-based negative electrode material in the cycled state, which is recorded as state A2.
[0072] (5) estimating the cycling performance of the electrode material based on the changes in the positron annihilation lifetime and intensity in the initial state and the positron annihilation lifetime and intensity in the cycled state;
[0073] Wherein, when △T1<2%, △I1<2%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is ≥400 cycles;
[0074] When 2%≤△T1<5%, 2%≤△I1<5%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is 200-399 cycles;
[0075] When 5%≤△T1<10%, 5%≤△I1, △T2<2%, △I2≥1%, the charge and discharge cycle life of the battery sample is 100-199 cycles;
[0076] When 10%≤△T1,△T2≥2%, the charge-discharge cycle life of the battery sample is ≤99 cycles;
[0077] The charge and discharge cycle life of the battery sample refers to the number of charge and discharge cycles required for the capacity retention rate of the battery sample to drop below 80% of the initial capacity when the battery sample is charged and discharged at the same rate in the charge and discharge cycle process in S4;
[0078]
[0079]
[0080]
[0081]
[0082] T1 is the short life in the initial state, and T1' is the short life in the post-cycle state;
[0083] T2 is the long life in the initial state, and T1′ is the long life in the post-cycle state;
[0084] I1 is the positron intensity 1 in the initial state, and I1' is the positron intensity 1 in the state after the cycle;
[0085] I2 is the positron intensity 2 in the initial state, and I2' is the positron intensity 2 in the state after the cycle.
[0086] More specifically, Table 1 shows the positron annihilation test results of state A1 and state A2.
[0087] Table 1
[0088] Life 1 (short life) Intensity 1 Life 2 (long life) Intensity 2 A1 0.231ns 26.4% 1.344ns 13.6% A2 0.269ns 25.5% 1.374ns 14.2% △ △T1=16.5% △I1=3.4% △T2=2.2% △I2=4.4%
[0089] According to the data changes from A1 to A2, we can draw the following conclusions:
[0090] Lifespan 1: The short lifespan increases significantly. The possible reason is that a lot of vacancy defects are generated inside the nano-silicon or the defect size increases.
[0091] Strength 1: The strength is slightly reduced. The possible reason is that a certain amount of nano-silicon is consumed, resulting in the formation of SEI film, etc., and the active substances of the negative electrode material are reduced.
[0092] Life span 2: Long life span may be due to the fact that nano-silicon, Super P and PVDF as negative electrode materials show an overall expansion trend, the density decreases, they become looser and the stability decreases.
[0093] Strength 2: The strength increased slightly. The possible reason is that small cracks may have appeared in the negative electrode material, accompanied by a small amount of electrolyte infiltration, which reduced the stability of the electrode.
[0094] In summary, after 10 cycles at a 1C rate, although the specific capacity of the pure nano-silicon powder (100nm) electrode material has not changed significantly, many microscopic defects may have appeared inside, the binder and the active material may have been peeled off to a certain extent, and the microstructure has suffered a certain degree of internal damage. Therefore, it is predicted that its cycle performance is not good. Further comparison can estimate that the cycle life of this electrode and material should be less than 100 cycles.
[0095] In order to verify the accuracy of the above estimation results, after step (4), the button half-cell was further charged and discharged for 90 cycles according to the method of step (3). At this time, the specific capacity of the button half-cell (i.e., the specific capacity after 100 charge and discharge cycles) was reduced to 34% of the initial state (specific capacity after the first charge and discharge), and the battery cycle life was short, less than 100 cycles, which is consistent with the conclusion of the above estimation method of the present invention.
[0096] Example 2
[0097] Example 1 was repeated except that porous nano-silicon powder (average particle size 100 nm, specific surface area 75 m 2 / g) to replace pure nano silicon powder.
[0098] Table 2 shows the positron annihilation test results of state A1 and state A2.
[0099] Table 2
[0100] Lifespan 1 Intensity 1 Lifespan 2 Intensity 2 A1 0.233ns 22.2% 1.304ns 15.1% A2 0.246ns 20.8% 1.311ns 15.3% △ △T1=5.6% △I1=6.3% △T2=0.5% △I2=1.3%
[0101] According to the data changes from A1 to A2, we can draw the following conclusions:
[0102] Lifetime 1: The short lifetime increases slightly. The possible reason is that a small amount of vacancy defects are generated inside the porous nano-silicon or the defect size increases slightly.
[0103] Strength 1: The strength decreases significantly. The possible reason is that a certain amount of nano-silicon is consumed, resulting in the formation of SEI film, etc., and the active substances of the negative electrode material are reduced.
[0104] Lifespan 2: There is basically no change in the long lifespan, indicating that nano-silicon, Super P and PVDF are stable as negative electrode materials.
[0105] Strength 2: The strength has basically not changed, indicating that the negative electrode material basically maintains stability.
[0106] In summary, after 10 cycles at a 1C rate, although the specific capacity of the porous nano-silicon powder electrode material has not changed significantly, a certain amount of microscopic defects have appeared inside, the active material has been consumed significantly, and the binder and the active material are stably combined. Therefore, its cycle performance is predicted to be good. Further comparison can estimate that the cycle life of the electrode and material should be higher than 100 cycles and lower than 200 cycles.
[0107] In order to verify the accuracy of the above estimation results, after step (4), the button half-cell was further charged and discharged for 190 cycles according to the method of step (3). At this time, the specific capacity of the button half-cell (i.e., the specific capacity after 200 charge and discharge cycles) was reduced to 77% of the initial state (specific capacity after the first charge and discharge), and the battery cycle life was relatively long, reaching 100-200 cycles, which is consistent with the conclusion of the above estimation method of the present invention.
[0108] Example 3
[0109] Example 1 was repeated, except that carbon nanotubes were used to coat porous nano-silicon powder (the average particle size of porous nano-silicon was 100 nm, and the specific surface area was 75 m 2 / g, the size after coating is about 120nm) to replace pure nano silicon powder. Carbon nanotubes were purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, multi-walled carbon nanotubes, outer diameter 4-8nm, purity>98%. The preparation method of carbon nanotube-coated porous nano silicon powder is as follows: weigh carbon nanotubes and porous nano silicon powder (mass ratio 1:1), put the weighed carbon nanotubes and nano silicon powder into a stainless steel ball mill, the mass ratio of stainless steel beads to materials is 119:1, fix the stainless steel ball mill on a planetary ball mill, set the ball milling speed to 600rpm, the ball milling time to 2h, and obtain carbon nanotube-coated porous nano silicon powder after ball milling.
[0110] Table 3 shows the positron annihilation test results of state A1 and state A2.
[0111] Table 3
[0112] Lifespan 1 Intensity 1 Lifespan 2 Intensity 2 A1 0.264ns 19.5% 1.418ns 19.6% A2 0.264ns 19.3% 1.420ns 19.7% △ △T1=0% △I1=1.0% △T2=1.4% △I2=0.5%
[0113] According to the data changes from A1 to A2, we can draw the following conclusions:
[0114] Lifespan 1: The short lifespan has basically not changed, indicating that there is no significant increase in the internal defects of the carbon nanotube-coated porous nanosilicon.
[0115] Strength 1: The strength decrease is not obvious, indicating that a very small amount of carbon nanotube-coated porous nano-silicon is consumed.
[0116] Lifespan 2: There is basically no change in the long lifespan, indicating that carbon nanotube-coated porous nano-silicon, Super P and PVDF are stable as negative electrode materials.
[0117] Strength 2: The strength has basically not changed, indicating that the carbon nanotube-coated porous nano-silicon negative electrode material basically maintains stability.
[0118] In summary, after 10 cycles at a 1C rate, the specific capacity of the carbon nanotube-coated porous nanosilicon electrode material has not changed significantly, the internal defects have not changed significantly, and the binder and active material are stably combined. Therefore, it is predicted that its cycle performance is excellent. Further comparison can estimate that the cycle life of the electrode and material should be higher than 400 cycles.
[0119] In order to verify the accuracy of the above estimation results, after step (4), the button half-cell was further charged and discharged for 390 cycles according to the method of step (3). At this time, the specific capacity of the button half-cell (i.e., the specific capacity after 400 charge and discharge cycles) was still maintained at 83% of the initial state (specific capacity after the first charge and discharge), and the battery cycle life was long, reaching more than 400 cycles, which is consistent with the conclusion of the above estimation method of the present invention.
[0120] In summary, the method of the present invention can accurately predict the cycle life range of electrode materials, which helps to more simply and quickly predict the cycle life performance of a certain electrode material, and provides convenience for the research and development of electrode materials.
[0121] Example 4
[0122] Fast prediction of LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 The cycle life of the positive electrode material. This test electrode is applied to the half-cell of a button-type lithium battery, including the following steps:
[0123] (1) Taking the average size of LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 Powder (fired in the laboratory, the firing method refers to the paper Fabrication of a LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 cathode for low-cost long-life lithium-ion batteries) as the active material, LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 , Super P (small particle conductive carbon black), and PVDF are mixed in a mass ratio of 8:1:1, and an appropriate amount of NMP (N-methylpyrrolidone, 15 drops of solvent are added to every 100 mg of the mixture) solvent is added to the resulting mixture, and the mixture is put into a mortar and ground into a slurry. The slurry is coated on aluminum foil, and the thickness of the positive electrode layer is 300 microns after drying, and the positive electrode sheet is obtained by cutting. The prepared positive electrode sheet is assembled into a button half-cell, and the assembly needs to be completed in a vacuum glove box with an argon atmosphere.
[0124] (2) After the battery assembly is completed, the button-type half-cell is clamped into a battery testing system (Xinwei CT-4008Tn), and the button-type half-cell is charged and discharged for the first time (0.5C) to allow the battery to reach an initial operating state.
[0125] (3) Place a point positron radiation source on the outer surface of the cathode of the button half-cell (i.e., close to the LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 A baffle is placed on the surface of the positron radiation source away from the outer surface to form a "sandwich" structure, and the "sandwich" structure is then placed in the acquisition probe of a positron annihilation lifetime spectrometer (TechAP positron annihilation spectrometer from Japan), and the positron annihilation lifetime spectrum is collected. The spectrum is analyzed by PALSfit3 spectrum analysis software. The annihilation lifetime of positrons in the radiation source itself, the battery casing, the aluminum foil, etc. is deducted during the spectrum analysis process (for general positron annihilation lifetime spectrum analysis methods, please refer to the spectrum analysis software download page: https: / / palsfit.dk / ) to obtain the positron annihilation lifetime and intensity in the silicon-based negative electrode material in the initial state, which is recorded as state A1.
[0126] (3) The button-type half-cell is clamped into the battery testing system described in step (2) and charged and discharged for 10 cycles at a rate of 1C.
[0127] At this time, the energy retention rate of the button half-cell is high, and the capacity decay is not obvious (the capacity retention rate is higher than 99%), and it is impossible to rely on conventional methods to judge the life of the electrode material.
[0128] (4) Take out the battery and place the point positron radiation source on the outer surface of the cathode of the button half-cell (i.e. close to the LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 A baffle (annealed nickel sheet, 0.1 mm thick, obtained by annealing a pure nickel sheet at 680° C. in argon for 10 hours) is placed on the surface of the positron radiation source away from the outer surface to form a "sandwich" structure. The "sandwich" structure is then placed in the acquisition probe of a positron annihilation lifetime spectrometer to collect a positron annihilation lifetime spectrum, which is then analyzed using PALSfit3 spectrum analysis software. The annihilation lifetime of the positron in the radiation source itself, the battery housing, the aluminum foil, etc. is deducted during the spectrum analysis process to obtain the LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2The positron annihilation lifetime and intensity in the middle of the positive electrode material are recorded as state A2.
[0129] (5) estimating the cycling performance of the electrode material based on the changes in the positron annihilation lifetime and intensity in the initial state and the positron annihilation lifetime and intensity in the cycled state;
[0130] Wherein, when △T1<2%, △I1<2%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is ≥400 cycles;
[0131] When 2%≤△T1<5%, 2%≤△I1<5%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is 200-399 cycles;
[0132] When 5%≤△T1<10%, 5%≤△I1, △T2<2%, △I2≥1%, the charge and discharge cycle life of the battery sample is 100-199 cycles;
[0133] When 10%≤△T1,△T2≥2%, the charge-discharge cycle life of the battery sample is ≤99 cycles;
[0134] The charge and discharge cycle life of the battery sample refers to the number of charge and discharge cycles required for the capacity retention rate of the battery sample to drop below 80% of the initial capacity when the battery sample is charged and discharged at the same rate in the charge and discharge cycle process in S4;
[0135]
[0136]
[0137]
[0138]
[0139] T1 is the short life in the initial state, and T1' is the short life in the post-cycle state;
[0140] T2 is the long life in the initial state, and T1′ is the long life in the post-cycle state;
[0141] I1 is the positron intensity 1 in the initial state, and I1' is the positron intensity 1 in the state after the cycle;
[0142] I2 is the positron intensity 2 in the initial state, and I2' is the positron intensity 2 in the state after the cycle.
[0143] More specifically, Table 4 shows the positron annihilation test results of state A1 and state A2.
[0144] Table 4
[0145] Life 1 (short life) Intensity 1 Life 2 (long life) Intensity 2 A1 0.173ns 18.6% 1.389ns 14.8% A2 0.176ns 18.8% 1.395ns 14.9% △ △T1=1.7% △I1=1.1% △T2=0.4% △I2=0.7%
[0146] According to the data changes from A1 to A2, we can draw the following conclusions:
[0147] Life 1: Short life has basically no change, indicating that LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 There was no significant increase in internal defects.
[0148] Strength 1: No decrease in strength, indicating that LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 Maintain stability.
[0149] Life 2: Long life has basically no change, indicating that LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 , Super P and PVDF are overall stable as negative electrode materials.
[0150] Strength 2: The strength is basically unchanged, indicating that LiNi 0.5 Mn 0.4 Ti 0.03 Mg 0.03 Nb 0.01 Mo 0.03 O 2 The positive electrode material basically maintains stability.
[0151] In summary, after 10 cycles at a rate of 1C, there is no obvious change in the internal defects, and the binder and active material are stably combined. Therefore, it is predicted that its cycle performance is excellent. Further comparison can estimate that the cycle life of the electrode and material should be higher than 400 cycles.
[0152] In order to verify the accuracy of the above estimation results, after step (4), the button half-cell was further charged and discharged for 390 cycles according to the method of step (3). At this time, the specific capacity of the button half-cell (i.e., the specific capacity after 400 charge and discharge cycles) was reduced to 91% of the initial state (specific capacity after the first charge and discharge), and the battery cycle life was long, exceeding 400 cycles, which is consistent with the conclusion of the above estimation method of the present invention.
[0153] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
Claims
1. A method for estimating the cycle performance of an electrode material of a rechargeable battery, characterized in that: The steps include: S1. Assembling the electrode materials to be tested to form a battery sample; Wherein, the battery sample is a half-battery or a full-battery; S2, charging and discharging the battery sample obtained in S1 for the first time; S3, placing a positron radiation source close to the outer surface of the battery sample, collecting the positron annihilation lifetime spectrum of the battery sample at this time, decomposing and fitting the spectrum, and obtaining the positron annihilation lifetime and intensity in the initial state; Wherein, the outer surface is the area of the outer shell of the battery sample close to the location of the electrode material; S4, performing a charge and discharge cycle on the battery sample for at least one cycle; S5, placing a positron radiation source close to the outer surface of the battery sample, collecting the positron annihilation lifetime spectrum of the battery sample at this time, decomposing and fitting the spectrum, and obtaining the positron annihilation lifetime and intensity in the cycled state; Wherein, the outer surface is the area of the outer shell of the battery sample close to the location of the electrode material; S6. Estimate the cycle performance of the electrode material according to the changes in the positron annihilation lifetime and intensity in the initial state and the positron annihilation lifetime and intensity in the cycled state.
2. The estimation method according to claim 1, characterized in that: In S3 and / or S5, a baffle is placed on the surface of the positron radiation source away from the outer surface to form a "sandwich" structure, and the "sandwich" structure is then placed in a collection probe of a positron annihilation lifetime spectrometer to collect a positron annihilation lifetime spectrum; Wherein, the baffle is made of a material with a known positron annihilation lifetime; Preferably, the baffle is a metal sheet, more preferably a nickel sheet; Preferably, the thickness of the baffle is ≥1 mm, more preferably 2-10 mm.
3. The estimation method according to claim 1, characterized in that: In S4, the cycle is 2-100 times, preferably 10-80 times.
4. The estimation method according to claim 1, characterized in that: In S4, the charge-discharge cycle rate is 0.1-10C, preferably 0.5-5C, and more preferably 1-3C.
5. The estimation method according to any one of claims 1 to 4, characterized in that: In S6, when △T1<2%, When △I1<2%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is ≥400 cycles; when 2%≤△T1<10%, 2%≤△I1, △T2<2%, the charge and discharge cycle life of the battery sample is 100-399 cycles; When 10%≤△T1,△T2≥2%, the charge-discharge cycle life of the battery sample is ≤99 cycles; The charge and discharge cycle life of the battery sample refers to the number of charge and discharge cycles required for the capacity retention rate of the battery sample to drop below 80% of the initial capacity when the battery sample is charged and discharged at the same rate in the charge and discharge cycle process in S4; T1 is the short life in the initial state, and T1' is the short life in the post-cycle state; T2 is the long life in the initial state, and T1′ is the long life in the post-cycle state; I1 is the positron intensity 1 in the initial state, and I1' is the positron intensity 1 in the state after the cycle; I2 is the positron intensity 2 in the initial state, and I2' is the positron intensity 2 in the state after the cycle.
6. The estimation method according to claim 5, characterized in that: When 2%≤△T1<5%, 2%≤△I1<5%, △T2<2%, △I2<1%, the charge and discharge cycle life of the battery sample is 200-399 cycles; When 5%≤△T1<10%, 5%≤△I1, △T2<2%, △I2≥1%, the charge and discharge cycle life of the battery sample is 100-199 cycles.
7. The estimation method according to any one of claims 1 to 4, characterized in that: The rechargeable battery includes one or more of a lithium battery, a sodium battery, a lead-acid battery, a nickel-cadmium battery, and a nickel-hydrogen battery; Preferably, the electrode material is a positive electrode material or a negative electrode material; the negative electrode material includes a silicon-based negative electrode material.
8. The estimation method according to any one of claims 1 to 4, characterized in that: The silicon-based negative electrode material includes one or more of nano silicon powder, porous nano silicon powder, and carbon nanotube-coated porous nano silicon powder.
9. The estimation method according to any one of claims 1 to 4, characterized in that: The positron radiation source is a point-shaped positron radiation source.
10. The estimation method according to any one of claims 1 to 4, characterized in that: In S2, the battery sample obtained in S1 is charged and discharged for the first time at a rate of 0.1-3C, preferably 0.3-1.5C, and more preferably 0.5-1C.
Citation Information
Cited By
Performance prediction method for modified layered oxide electrode material
CN121090606A
